Selective enrichment of bacterial pathogens by microplastic biofilm - Wu, Xiaojian; Pan, Jie; Li, Meng; Li, Yao; Bartlam, Mark; Wang, Yingying (Water research (Oxford), 2019)
Microplastics have been found to be ubiquitous in freshwater ecosystems, providing a novel substrate for biofilm formation. Here, we incubated biofilm on microplastics and two natural substrates (rock and leaf) under a controlled environment to investigate the differences of microbial community structure, antibiotic resistance gene (ARG) profiles, and ARG microbial hosts between biofilms on three types of substrates. Results from high-throughput sequencing of 16S rRNA gene revealed that microplastic biofilm had a distinctive community structure. Network analyses suggested that microplastic biofilm possessed the highest node connected community, but with lower average path length, network diameter and modularity compared with biofilm on two natural particles. Metagenomic analyses further revealed microplastic biofilm with broad-spectrum and distinctive resistome. Specifically, according to taxonomic annotation of ARG microbial hosts, two opportunisitic human pathogens (Pseudomonas monteilii, Pseudomonas mendocina) and one plant pathogen (Pseudomonas syringae) were detected only in the microplastic biofilm, but not in biofilms formed on natural substrates. Our findings suggest that microplastic is a novel microbial niche and may serve as a vector for ARGs and pathogens to new environment in river water, generating freshwater environmental risk and exerting adverse impacts on human health. [Display omitted] •Microplastic biofilm has unique microbial community structure.•Distinctive antibiotic resistance genes were detected in the microplastic biofilm.•Opportunistic human pathogens were enriched in microplastic biofilm.